Study of the removal and control of iron in the waters of the spring Serra do Andrade-MG (Research, Society and Development, 2021)
One of the basic needs for human survival is the consumption of drinking water, since in addition to being used for drinking it is also indispensable in food preparation and in hygiene and cleaning processes. Therefore, it is necessary for the water to be within the potability standards required by the Ministry of Health (MS), which assigned to Portaria 518, of March 25, 2004, the control and surveillance of water quality. The present study had as main objective to propose an alternative process for the removal of iron (Fe) in the waters of the Serra do Andrade spring - Minas Gerais, by means of adsorptive filtration with the application of the adsorbent material (zeolite). As a theoretical framework, a dialogue was established between the authors who brought a load of important information to this area of ​​research, such as Simão et. al (2020), Vistuba (2010), Carmo (2013), and Cali and Costa (2020). The methodological procedures chosen to make the study possible were, first, document analysis for data collection, practice for collecting water samples in the first and second phase of the study and a final analysis of the research. A practical study was carried out on the use of zeolite in an attempt to remove iron ions in the form of precipitates. As results obtained, it was possible to perceive the importance of new alternative sources of iron removal and control in mainly natural waters and it can also be said that the studied adsorbent material, zeolite, proved to be very efficient in removing Fe.